2021
DOI: 10.1096/fj.202002566r
|View full text |Cite
|
Sign up to set email alerts
|

Role of TCF‐1 in differentiation, exhaustion, and memory of CD8 + T cells: A review

Abstract: T cell factor-1 (TCF-1) (encoded by the TCF7 gene) is a transcription factor that plays important role during the T cell development and differentiation for T cell to exercise its functions including producing memory T cells. Not only TCF-1 can modulate the T cell development but also exerts various effects on the differentiation and function of mature CD8 + T cells. In addition, it drives the production and maintenance of the immune response of CD8 + T cells after PD-1 checkpoint blockade therapy. TCF-1 can s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 111 publications
(288 reference statements)
1
29
0
Order By: Relevance
“…Interestingly, CD4 + memory T cells shared an upregulated expression pattern of TFs with CD8 + memory T cells, such as BCLAF1, TCF7, and FOXP1, implying the potential roles of these TFs in regulating the translational initiation in the biological process ( Figure 5H ). Previous studies have indicated that TCF7 and FOXP1 contribute to the development and homeostasis of memory T cells ( 28 , 29 ). CD4 + effector and CD8 + effector T cells also shared some upregulated TFs, including PRDM1, RORA, and KLF6, while CEBPB, CEBPD, CREM, EOMES, and TBX21 were upregulated only in CD8 + effector T cells, which were mainly associated with “regulation of transcription” ( Figure 5I ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, CD4 + memory T cells shared an upregulated expression pattern of TFs with CD8 + memory T cells, such as BCLAF1, TCF7, and FOXP1, implying the potential roles of these TFs in regulating the translational initiation in the biological process ( Figure 5H ). Previous studies have indicated that TCF7 and FOXP1 contribute to the development and homeostasis of memory T cells ( 28 , 29 ). CD4 + effector and CD8 + effector T cells also shared some upregulated TFs, including PRDM1, RORA, and KLF6, while CEBPB, CEBPD, CREM, EOMES, and TBX21 were upregulated only in CD8 + effector T cells, which were mainly associated with “regulation of transcription” ( Figure 5I ).…”
Section: Resultsmentioning
confidence: 99%
“…TCF7, an active transcription factor associated with the Wnt mediator β-catenin, was induced by basic fibroblast growth factor (bFGF) treatment in fibroblasts (Wang X. et al, 2017). TCF-7 plays an important regulatory role in mature naive CD4 + and CD8 + T cell differentiation, which might participate in the immune response during tissue expansion (Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Both studies observed that T-cell-targeting escaped epitopes had a diminished expression of the activation marker CD38, intermediate expression of PD-1, which is an activation but also regulatory protein, and a rather high expression of CD127, the receptor of IL-7a that is important for homeostasis [73,74]. Correspondingly, these CD8+ T cells expressed a low level of the transcription factor T-bet and Eomes and a high amount of TCF1, a transcription factor that defines memory-like cells with proliferative potential [112]. This observation is in line with findings in HCV and HIV infection, where the loss of antigen recognition mediated by viral escape led to the formation of a T cell subset that is similar to the memory T cell compartment in acute-resolving infection and that was called memorylike [110,111,113,114].…”
Section: Viral Escapementioning
confidence: 99%